Assessment of radiological signs and epidemiology of congenital heart disease among Egyptian children undergoing multi-detector computed tomography - Ayat Mousa; Mohamed Ali Salem; Rania Hegazy; Hassan Elkiki (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Congenital heart disease (CHD) is a leading cause of infant morbidity and mortality worldwide, with a prevalence of approximately 8 per 1,000 live births. Multi-detector computed tomography (MDCT) has emerged as a crucial imaging tool, providing detailed anatomical visualization of cardiac structures, particularly in cases requiring preoperative assessment. Methods A retrospective analysis of CHD patients was conducted, assessing demographic characteristics, disease classification, and MDCT findings. Statistical data and radiological images from a 2-year study period were analyzed to determine the role of MDCT in CHD diagnosis. Results Of 619 patients analyzed, 61% were male and 39% were female. Cyanotic CHD accounted for 55% of cases, with tetralogy of Fallot (TOF) being the most prevalent (64.3%). Acyanotic CHD made up 45%, with coarctation of the aorta (16%) and left-to-right shunts (13.6%) being the most common. MDCT demonstrated superior diagnostic capability in assessing extracardiac vascular anomalies and complex CHD subtypes. Conclusions MDCT is a valuable adjunct to echocardiography in CHD evaluation, particularly for surgical planning. Despite concerns about radiation exposure, its high spatial resolution and three-dimensional reconstruction capabilities make it indispensable for complex CHD assessment.